Synthesis and Antimicrobial Activity of 1-(Phenyl)-3-(4'-chlorophenyl)-5-(arylsubstituted)-2-pyrazoline - Srinivasa Rao, N.; Rao, J.T. (Asian Journal of Chemistry, 2016)
1-(Phenyl-3-(4'-chlorophenyl-5-(arylsubstituted-2-pyrazoline has been synthesized by cyclization of 1-(arylsubstituted-3-(4'-chlorophenyl)-1-propene-3-one with phenyl hydrazine in presence of glacial acetic acid. The pyrazoline derivatives have been screened for their antimicrobial acitivity against E. coli, B. subtilis, Trichoderma sp. and Aspergillus niger.